2020
DOI: 10.31557/apjcp.2020.21.2.363
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic Extract of Ocimum sanctum Leaves Reduced Invasion and Matrix Metalloproteinase Activity of Head and Neck Cancer Cell Lines

Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) has a yearly incidence of 600,000 cases worldwide with a low survival rate. Ocimum sanctum L. or Ocimum tenuiflorum L. (Holy basil; Tulsi in Hindi), is a traditional medicine herb that demonstrates numerous effects including anti-oxidant, anti-microbial, and anti-tumor effects. The aim of this study was to evaluate the anti-invasive effect of O. sanctum leaf extract on HNSCC cell lines. Methods: Ethanolic extract of O. sanctum leaf (EEOS) was prepared a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 26 publications
(32 reference statements)
0
25
0
Order By: Relevance
“…Several previous studies have shown cytotoxic and anti-metastasis activity of O. tenuiflorum extracts on a variety of cancer cell lines. The ethanolic extract of O. sanctum (EEOS) demonstrated growth inhibitory activity against several cancer cell types including human non-small cell lung carcinoma (A549) [ 10 , 25 ], prostate cancer cells [ 9 ], and head and neck squamous cell carcinoma (HNSCC) [ 26 ]. Similarly, Manaharan et al found that the purified essential oil from O. sanctum (OSEO) inhibited cell proliferation of human breast cancer cells (MCF-7); their IC 50 value of 170 µg/mL was similar to our result [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have shown cytotoxic and anti-metastasis activity of O. tenuiflorum extracts on a variety of cancer cell lines. The ethanolic extract of O. sanctum (EEOS) demonstrated growth inhibitory activity against several cancer cell types including human non-small cell lung carcinoma (A549) [ 10 , 25 ], prostate cancer cells [ 9 ], and head and neck squamous cell carcinoma (HNSCC) [ 26 ]. Similarly, Manaharan et al found that the purified essential oil from O. sanctum (OSEO) inhibited cell proliferation of human breast cancer cells (MCF-7); their IC 50 value of 170 µg/mL was similar to our result [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Kwak et al demonstrated through molecular analysis that the anti-metastatic mechanism of EEOS is mediated by the inhibition of phosphatidylinositide 3-kinases (PI3K)/Akt in non-small cell lung cancer cells [ 27 ]. Meanwhile, treatment of HNSCC with EEOS resulted in a significant inhibition of cell invasion due to attenuating the activity of matrix metalloproteinase (MMP)-2 and MMP-9 [ 26 ]. Our in vitro results clearly extend the significant inhibitory effect of OTEO treatment on cancer cell viability and metastasis to human gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxicity of EAEP on the HNSCC cell lines was investigated using the methyl thiazotetrazolium (MTT) as previously described ( Utispan et al, 2020 ). Basically, the incubation periods for the MTT assay were 24, 48, or 72 h. However, tumor cells are very heterogenous and their doubling times vary.…”
Section: Methodsmentioning
confidence: 99%
“…O. sanctum ethanolic extract at a concentration of 0.4 mg/mL inhibited matrix metalloproteinase (MMP)-2 activity in HN12 and HN4 cells by 71% and 65%, respectively, and MMP-9 activity in HN12 and HN4 cells by 85% and 44%, respectively. The invasion activity of HN12 and HN4 cells was inhibited by 30% in comparison with that of the control ( p < 0.05), but no significant changes were observed in HN31 and HN30 cells [ 37 ]. In a recent study, the anticancer activity of O. sanctum was examined in the OSCC cell line Ca9–22.…”
Section: Plants With Beneficial Effects Against Oral Cancermentioning
confidence: 99%